Regionális multiplikáció és egy alkalmazása - Kotosz, Balázs (Jelenkori Társadalmi és Gazdasági Folyamatok, 2013)
The export base theory is really based on the regional mulliplicator theory of international economy. In the paper, we step over the usual textbook examples and show how the mulliplicator can be less than one, practically decreasing local income. We also analyze a special multiplication process, in particular the role of higher education institutions. The impact of higher education institution on local economy is extensively wide. Universities have important impact on the input and the output side, or on the demand and supply side, also. Beck et al (1995) define economic impact as „the difference between existing economic activity in a region given the presence of the institution and the level that would have been present if the institution did not exist." There are many approaches of the analysis of the regional impacts, the most important and most widely used is the Keynesian mulliplicator approach.